Composición taxonómica y relaciones zoogeográficas de los peces demersales de la costa occidental de Baja California Sur, México - Rodríguez Romero, Jesús (2008)
The composition of demersal fish along the western coast of the State of Baja California Sur, México, including the limit of the northern distribution of the ichthyofauna of the eastern tropi-cal Pacific, is presented. The survey was carried out on four oceanographic cruises between autumn 2004 and March 2006. Of 220 species in 132 genera and 73 families, 26.3% are species of wide distribution from San Diego County, USA to Panama and 21.7% are species restricted to the eastern tropical Pacific. Six species are new findings for the area or range expansions. The families with the most species are Paralichthyidae and Scorpaenidae, each with 16 species. The most frequent genus was Sebastes, with nine species. We present a table with common Spanish names, size range and status of each species inside the community.